2019
DOI: 10.1021/acs.nanolett.9b00300
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying To Produce Efficacious CPMV Virus-like Particles

Abstract: In situ cancer vaccination that uses immune stimulating agents is revolutionizing the way that cancer is treated. In this realm, viruses and noninfectious virus-like particles have gained significant traction in reprogramming the immune system to recognize and eliminate malignancies. Recently, cowpea mosaic virus-like particles (VLPs) have shown exceptional promise in their ability to fight a variety of cancers. However, the current methods used to produce CPMV VLPs rely on agroinfiltration in plants. These pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
13
0
3
Order By: Relevance
“…DLS and TEM data were consistent with the intact CPMV being released from the polymer blends ( Figure S3 ); however, the lyophilization step resulted in loss of the RNA cargo ( Figure S2 ), which is consistent with our previous findings. 63 CPMV genomic RNA has been identified as a TLR-7 agonist, and its absence during antigen processing can mitigate the self-adjuvant properties of CPMV vaccines. 55 The difference of the antibody titers of CPMV implants compared to prime-boost formulations requires further analysis and may reflect a combination of RNA loss or other structural changes that influence subsequent interactions with (and activation of) innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…DLS and TEM data were consistent with the intact CPMV being released from the polymer blends ( Figure S3 ); however, the lyophilization step resulted in loss of the RNA cargo ( Figure S2 ), which is consistent with our previous findings. 63 CPMV genomic RNA has been identified as a TLR-7 agonist, and its absence during antigen processing can mitigate the self-adjuvant properties of CPMV vaccines. 55 The difference of the antibody titers of CPMV implants compared to prime-boost formulations requires further analysis and may reflect a combination of RNA loss or other structural changes that influence subsequent interactions with (and activation of) innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…For the loading of CpG-ODN into PhMV VLPs, purified VLPs were lyophilized and redispersed in D.I. water, followed by treatment with RNase A to remove the residual host RNA; we previously reported this as an effective method to remove RNA from CPMV [36]. The rat-derived HER2 epitope CH401 (sequence 163YQDMVLWKDVFRKNNQLAPV182-GPSL-N 3 , representing amino acid residues 163-182) were conjugated to the external surface of the VLPs, using copper-free click chemistry.…”
Section: Preparation Of Vlps and Vaccine Formulationmentioning
confidence: 99%
“…The crystal structure indicated that four Lys side chains (K62, K143, K153, and K166) were exposed on the external surface of each coat protein, offering 720 potential conjugation sites. Purified PhMV VLPs were freeze dried by negative pressure lyophilization to dehydrate the VLPs and eject the RNA, based on our previous method [36]. The obtained powder was redispersed in D.I.…”
Section: Synthesis and Characterization Of The Vlp-based Her2 Vaccine...mentioning
confidence: 99%
“…A further model of the anti-melanoma vaccine is based on the use of cowpea mosaic virus-like particles (CPMV-VLPs), which showed promising results as an immune stimulating agent for in situ cancer vaccination [104]. Two VLP constructions have been developed: one is based on the complete CMPV virion, including the genomic RNA; the second is based on the empty CPMV virion [113].…”
Section: Vlps For Melanomamentioning
confidence: 99%